Springer handbook of nanotechnology - Bhushan, Bharat 1949-.; Gale Group (Berlin Springer, 2007)
"A definitive reference book in the nanoscience and nanotechnology area. It integrates the knowledge from nanofabrication, nanodevices, nanomechanics, nanotribology and much more."--Publisher's description.
Introduction -- Nanostructures, micro/nanofabrication and materials -- MEMS/NEMS and BioMEMS/NEMS -- Scanning probe microscopy -- Nanotribology and nanomechanics -- Molecularly thick films for lubrication -- Industrial applications -- Micro/nanodevice reliability -- Technological convergence and governing nanotechnology.
Electronic reproduction.
Keywords: Nanotechnology -- Handbooks, manuals, etc; Electronic books